COMPARISON OF OXYGEN–INDUCED RADICAL INTERMEDIATES IN iNOS OXYGENASE DOMAIN WITH THOSE FROM nNOS and eNOS - Berka, Vladimir (2014)
Inducible nitric-oxide synthase (iNOS) produces the reactive oxygen and nitrogen species (ROS/RNS) involved in bacteria killing and is crucial in the host defense mechanism. However, high level ROS/RNS can also be detrimental to normal cells and thus their production has to be tightly controlled. Availability or deficiency of tetrahydrobiopterin (BH(4)) cofactor and L-arginine substrate control coupling or uncoupling of NOS catalysis. Fully coupled reaction, with abundant BH(4) and L-arginine, produces NO whereas the uncoupled NOS (in the absence of BH(4) and/or L-arginine) generates ROS/RNS. In the current work we focus on direct rapid freeze EPR to characterize the structure and kinetics of oxygen-induced radical intermediates produced by ferrous inducible NOS oxygenase domain (iNOS(ox)) in the presence or absence of BH(4) and/or L-arginine. Fully reconstituted iNOS(ox) (+BH(4), +L-Arg) forms a dimer and yields a typical BH(4) radical that indicates coupled reaction. iNOS(ox) (–BH(4)) remains mainly monomeric and produces exclusively superoxide, that is only marginally affected by the presence of L-arginine. iNOS(ox) (+BH(4), −L-Arg) exists as a monomer/dimer mixture and yields both BH(4) radical and superoxide. Present study is a natural extension of our previous work on the ferrous endothelial NOS(ox) (eNOS(ox)) [V. Berka, G. Wu, H.C. Yeh, G. Palmer, A.L. Tsai, J. Biol. Chem. 279 ( 2004) 32243–32251] and ferrous neuronal NOS(ox) (nNOS(ox)) [V. Berka, L.H. Wang, A.L. Tsai, Biochemistry 47 (2008) 405–420]. Overall, our data suggests different regulatory roles of L-arginine and BH(4) in the production of oxygen-induced radical intermediates in NOS isoforms which nicely serve individual functional role.